2016
DOI: 10.1002/1873-3468.12096
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor (Fgf) 23 gene transcription depends on actin cytoskeleton reorganization

Abstract: Edited by Lukas Alfons HuberThe consequence is a decrease in the plasma concentration of phosphate and 1,25(OH) 2 D 3 , the biologically active form of vitamin D. To mediate these renal effects, FGF23 requires aKlotho as a co-receptor [4,5].In addition, FGF23 is a powerful counteracter of aging. Mice deficient for FGF23 or for aKlotho suffer from rapid aging with a life span of a few weeks only and numerous age-related diseases [5,6]. The rapid aging is directly or indirectly dependent on the hyperphosphatemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 80 publications
1
16
0
Order By: Relevance
“…Notably, vitamin D has been shown to regulate the actin cytoskeleton in numerous cell types. In osteoblast-like cells, vitamin D promotes actin polymerization as part of its transcriptional induction of fibroblast growth factor 23 (Fajol et al 2016). In endometrial cells, vitamin D treatment has also been shown to induce changes in actin architecture, through regulation of the RAc1/Pak1 axis (Zeng et al 2016).…”
Section: A Role For Vitamin D In Evt Invasion?mentioning
confidence: 99%
“…Notably, vitamin D has been shown to regulate the actin cytoskeleton in numerous cell types. In osteoblast-like cells, vitamin D promotes actin polymerization as part of its transcriptional induction of fibroblast growth factor 23 (Fajol et al 2016). In endometrial cells, vitamin D treatment has also been shown to induce changes in actin architecture, through regulation of the RAc1/Pak1 axis (Zeng et al 2016).…”
Section: A Role For Vitamin D In Evt Invasion?mentioning
confidence: 99%
“…The function of KDM2B depends on the co-operation with Polycomb Repressor Complex-2 (PRC-2) that enables MEFs to undergo immortalization [4]. KDM2B is regulated by the basic fibroblast growth factor (bFGF) in human tumors that in turn governs various tumor characteristics including cell growth, migration, invasiveness, angiogenesis and actin cytoskeleton organization [5-7]. A previous study reported control of cell migration and angiogenesis by KDM2B in HUVECs [6].…”
Section: Introductionmentioning
confidence: 99%
“…Effects of 1α,25(OH) 2 D 3 include reorganization of actin cytoskeleton [11][12][13][14]. Apparently depending on the cell type, 1α,25(OH) 2 D 3 may either increase [11,12,14] or decrease [13] actin polymerisation.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently depending on the cell type, 1α,25(OH) 2 D 3 may either increase [11,12,14] or decrease [13] actin polymerisation. Early and/or late actin restructuring, following modifications of actin polymerization dynamics equilibrium, is a cellular response initiated by various signals including growth factors and cytokines [15][16][17], hormones [18][19][20][21] and ions [22,23].…”
Section: Introductionmentioning
confidence: 99%